Relationship between dynamic changes in remnant cholesterol and cardiovascular disease in middle-aged and older Chinese: a national cohort study - Zhang, Bin; Ma, Dengfeng; Pei, Zhiqiang; Ren, Qian; Qiu, Jin (Frontiers in Cardiovascular Medicine, 2025)
AimEpidemiological and genetic studies have shown that elevated basal remnant cholesterol (RC) levels increase cardiovascular disease (CVD) risk. However, the relationship between RC dynamics and CVD remains unclear. We aimed to investigate the relationship between the dynamic changes in RC and CVD occurrence in middle-aged and elderly populations in China.Methods and resultsThis cohort study investigated data from the study population of the 2011 and 2015 China Health and Retirement Longitudinal Study (CHARLS) and included 4,431 participants aged ≥45 years who provided complete information on RC and the occurrence or absence of CVD. Based on the change in RC in the population from 2011 to 2015, this study categorized the population into clusters 1, 2, and 3 using k-means cluster analysis. The relationship between baseline RC and CVD risk was examined using receiver operating characteristic (ROC) curves and restricted cubic spline (RCS) analysis. Logistic regression was used to explore the association between dynamic changes in RC levels and CVD risk, and subgroup analyses and sensitivity analyses were performed. There were 132 new cases of CVD among the 4,431 participants [2,386 women [53.85%] and 2,045 men [46.15%]; follow-up time, 4 years]. The area under the ROC curve for baseline RC in CVD was 0.534. RCS regression showed a linear association between RC at baseline and CVD. Logistic regression results showed a significantly increased CVD risk in Cluster 3 compared with Cluster 1 after correction for confounders (OR = 1.69, 95%CI: 1.13–2.55, P = 0.012); similarly, the risk of heart disease was significantly increased in Cluster 3 (OR = 1.76, 95%CI: 1.13–2.76, P = 0.012). Subgroup analyses showed a higher CVD risk in participants with baseline renal disease (OR = 15.34, 95%CI: 1.2–195.35, P = 0.035) and an interaction between RC change and body mass index (P for interaction = 0.038). Age-stratified analysis revealed a small difference in baseline RC between age groups (difference = −1.01 mg/dl, 95% CI: 0.08 to 1.94, P = 0.0328). RC showed the strongest correlation observed with TG (r = 0.80, p < 0.001).ConclusionsIn middle-aged and older Chinese participants, increased dynamic RC predicts increased CVD risk. Therefore, continuous monitoring of changes in RC levels is needed to reduce the risk of CVD.Lay summaryThis cohort study, including 4,431 middle-aged and elderly Chinese individuals, found that dynamically elevated remnant cholesterol was significantly associated with a 1.69-fold higher cardiovascular disease incidence, suggesting that dynamically elevated remnant cholesterol predicts a higher risk of cardiovascular disease in China's middle-aged and elderly population.